2008
DOI: 10.1136/ard.2007.074948
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations in the serotonin 5-HT2A receptor gene (HTR2A) are associated with rheumatoid arthritis

Abstract: In our study, genetic polymorphisms at the HTR2A gene are associated with susceptibility for RA, suggesting possible links between the serotonergic system and development of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 18 publications
0
24
1
1
Order By: Relevance
“…However, because not all four SNPs were genotyped in the NARAC study, we decreased the number of SNPs to two. As could be seen from Table 2, the TC haplotype based on rs6314 and rs1328674, which is part of what was previously reported to be in association with RA, 16 demonstrates a protective effect in the EIRA study (P¼0.005 in w 2 -test). Further, we addressed the hypothesis for association in two other study populations that was replicated in the NARAC study (P¼0.006 in w 2 -test) but not in the Leiden EAC study (P¼0.8206 in w 2 -test), although the control group had a 0.2% higher frequency compared with the patients group ( Table 2).…”
Section: Resultsmentioning
confidence: 75%
See 4 more Smart Citations
“…However, because not all four SNPs were genotyped in the NARAC study, we decreased the number of SNPs to two. As could be seen from Table 2, the TC haplotype based on rs6314 and rs1328674, which is part of what was previously reported to be in association with RA, 16 demonstrates a protective effect in the EIRA study (P¼0.005 in w 2 -test). Further, we addressed the hypothesis for association in two other study populations that was replicated in the NARAC study (P¼0.006 in w 2 -test) but not in the Leiden EAC study (P¼0.8206 in w 2 -test), although the control group had a 0.2% higher frequency compared with the patients group ( Table 2).…”
Section: Resultsmentioning
confidence: 75%
“…35 Partition of RA into ACPA-positive and ACPA-negative subtypes is adequate, as more evidence points toward the fact that these two subtypes differ in etiology and pathophysiology. In this paper, we have shown that HTR2A, recently found to be in association with RA, 16 interacts with HLA-DRB1 SE alleles in the ACPA-positive group of patients. HLA-DRB1 SE alleles have no effect on the development of ACPAnegative RA and that could be the reason why this interaction is not observed in this subgroup of the disease.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations